Heparin-binding epidermal growth factor-like growth factor protects rat intestine after portal triad clamping. (April 2013) - Liao, Xinxin; Chen, Liyan; Fu, Wenguang; Zhou, Jie
<x xml:space="preserve">Abstract</x> Heparin-binding epidermal growth factor-like growth factor (HB-EGF) is a potent mitogen and chemotactic factor. HB-EGF attenuates intestinal ischemia/reperfusion injury caused by superior mesenteric artery occlusion. We examined whether HB-EGF offers protection against intestinal congestion/reperfusion (C/R) injury, which is caused by portal triad clamping. Male Sprague–Dawley rats were randomly divided into three equally sized groups: I, sham-operated; II, portal triad clamping (Pringle maneuver); III, II + intraluminal administration of HB-EGF. Compared with sham-operated rats, all rats in group II exhibited significant increases in intestinal histologic injury, pro-inflammatory cytokine expression, myeloperoxidase activity, malonaldehyde levels, and apoptosis indices. Intraluminal administration of HB-EGF in group III significantly reduced these indicators when compared with group II. Clamping of the portal triad followed by reperfusion causes intestinal C/R injury and intraluminal administration of HB-EGF reduces the severity of intestinal C/R injury in rats.